La mesure de l'école : politique des standards et management par la qualité - Romuald Normand (Les éditions de la Maison des sciences de l'Homme, 2005)
Using evident illustrations, this paper aims to demonstrate how the quest for performance is related to rationalisation of educational systems where assessment plays a central role. Assessment is supported and used by management to raise standards and to improve basic skills of pupils in learning. In fact, the cult of efficiency and quality corresponds to the basement of a conservative reform policy which tends to increase economic competitiveness, with major effects on teaching and teachers.